A single-phase seven-level switched capacitor with common ground inverter and improved phase-shift modulation technique - Bisma Saif; Adil Sarwar; Shafiq Ahmad; Shiue-Der Lu; Hwa-Dong Liu (Scientific Reports)
Abstract Lately, transformer-less Researchers in the fields of power electronics and renewable energy have taken notice of photovoltaic inverters because of their great efficiency, low cost, and small size. However, higher efficiency typically results in more components, making the inverter costly and bulky. This article proposes a single-phase seven-level transformer-less with common ground topology. The proposed topology utilizes 10 switches, 4 capacitors and 1 diode. This article also suggests an improved Phase Shift (PS) Modulation Technique which reduces overall losses. When implemented with improved Phase Shift (PS), the total highest attainable efficiency of the proposed topology is 98.05% at 15 W. The THD% of voltage harmonics is reduced to 15.29% from 17.20% and for current harmonics is reduced to 5.07% from 10.15%. The reliability of the proposed inverter has also been analyzed. The simulation as well as hardware results have been presented to validate the performance of the proposed inverter.